2014
DOI: 10.1063/1.4892082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of slippage breakdown for a superhydrophobic microchannel

Abstract: A full characterization of the water flow past a silicon superhydrophobic surface with longitudinal micro-grooves enclosed in a microfluidic device is presented. Fluorescence microscopy images of the flow seeded with fluorescent passive tracers were digitally processed to measure both the velocity field and the position and shape of the liquid-air interfaces at the superhydrophobic surface. The simultaneous access to the meniscus and velocity profiles allows us to put under a strict test the no-shear boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 38 publications
3
73
1
Order By: Relevance
“…An immediate observation is that, as φ increases, the slip associated with a no-shear surface decreases while the slip associated with a no-slip surface increases. In two experiments, referred to as M1 and M2, Bolognesi et al (2014) observed that a more depressed groove associated with experiment M1 is associated with a larger slip length than experiment M2, where the interface invaded the groove to a lesser degree. As those authors pointed out, this is precisely not what is expected if the meniscus is a no-shear surface.…”
Section: Comparison Of No-slip and No-shear Assumptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…An immediate observation is that, as φ increases, the slip associated with a no-shear surface decreases while the slip associated with a no-slip surface increases. In two experiments, referred to as M1 and M2, Bolognesi et al (2014) observed that a more depressed groove associated with experiment M1 is associated with a larger slip length than experiment M2, where the interface invaded the groove to a lesser degree. As those authors pointed out, this is precisely not what is expected if the meniscus is a no-shear surface.…”
Section: Comparison Of No-slip and No-shear Assumptionsmentioning
confidence: 99%
“…As those authors pointed out, this is precisely not what is expected if the meniscus is a no-shear surface. Bolognesi et al (2014) went on to suggest that the observed behaviour is more consistent with the meniscus being a no-slip surface. From figure 3 of Bolognesi et al (2014), we fitted our theoretical profiles to the experimental meniscus profiles by visually estimating the geometrical parameters d/c = 1.5 µm/16 µm for experiment M1 and d/c = 0.8 µm/16 µm for experiment M2.…”
Section: Comparison Of No-slip and No-shear Assumptionsmentioning
confidence: 99%
See 3 more Smart Citations